Accuracy analysis of GO UTD radio-channel modeling in indoor scenarios at 1.8 and 2.5 GHz. - Loredo, Susana (IEEE Antennas & propagation magazine.)
Ray-tracing techniques have been widely used as simulation tools for the design and planning of wireless systems, both in urban microcells and in indoor picocells, due to the site-specific nature of those environments. However, the value of such tools depends on the accuracy of the predictions when compared to measurements in real-world propagation environments. In this paper, the accuracy of a ray-tracing technique based on a full three-dimensional implementation of GO/UTD is analyzed, by comparison between measurements and simulations carried out for different indoor wireless-propagation environments and in different frequency bands. The narrowband analysis shows that both the mean level of the received signal and the statistical behavior of its variations about the mean can be accurately estimated. In the wideband analysis, the comparison between measured and simulated power-delay profiles shows that both the amplitude and arrival times of the main multipath components can be well predicted. The statistical distributions of the measured and simulated wideband parameters are also compared, showing good agreement.